Lying particles - Vaidman, Lev (Frontiers in Quantum Science and Technology, 2024)
The common feature of several experiments, performed and proposed, in which particles provide misleading evidence about where they have been, is identified and discussed. It is argued that the experimental results provide a consistent picture when interference amplification effects are taken into account.